STRATEGI KOMUNIKASI PEMASARAN CAFE MERCI DALAM MENGATASI PERSAINGAN COFFEE SHOP DI KAVLING DPR SIDOARJO (Universitas Negeri Surabaya, 2023)
The Sidoarjo DPR Plot which is an area filled with coffee shops along the Sidoarjo DPR Plot road. This study aims to find out how and what strategies are carried out by Café Merci which is one of the coffee shops in the DPR Sidoarjo Lot. This study uses a qualitative research method with a case study approach. The results show that Café Merci uses a variety of strategies starting from the product aspects they have, namely the menus sold, the prices given to their products, then promotions are carried out to inform and also influence consumers, through aspects of choosing a location in the Sidoarjo DPR Plot. The marketing communication strategy carried out by Café Merci is in accordance with the marketing mix by Philip Kotler et al., (2018), namely 4p (product, price, place, and promotion). The conclusion of this study is that the communication strategy implemented by Café Merci has been successful in overcoming competition in the DPR plots, as evidenced by Café Merci, which still gets consumers from when it opened until now and gains loyalty from consumers who have come to Café Merci